A Google-Proof Collection of French Winograd Schemas - Pascal Amsili; Olga Seminck (Proceedings of the 2nd Workshop on Coreference Resolution Beyond OntoNotes (CORBON 2017), co-located with EACL 2017, 2017)
This article presents the first collection of French Winograd Schemas. Winograd Schemas form anaphora resolution problems that can only be resolved with extensive world knowledge. For this reason the Winograd Schema Challenge has been proposed as an alternative to the Turing Test. A very important feature of Winograd Schemas is that it should be impossible to resolve them with statistical information about word co-occurrences: they should be Google-proof. We propose a measure of Google-proofness based on Mutual Information, and demonstrate the method on our collection of French Winograd Schemas.